Towards tandem bio-chemo catalytic systems for the activation of alkanes and subsequent oxidation of alcohols to aldehydes using biofabricated Pd and Au catalysts - Govender, Mivashya (Centre for Bioprocess Engineering Research, 2022)
Alkane activation is known to be difficult due to the stable, saturated nature of the C-H bonds. Typical C-H bond activation techniques use harsh conditions, toxic solvents and excessive amounts of energy to produce low-value fuels and solvents. To develop value from the alkane feedstock and promote sustainable chemical manufacture, bio-catalysts are considered for terminal bond activation. This has been successfully demonstrated for the conversion of n-octane to 1-octanol using cytochrome P450 enzymes (Gudiminchi et al., 2012; Julsing et al., 2008; Meissner, 2013; Olaofe, 2013; Pennec et al., 2014). However, due to the low conversion and lowervalue of the alcohol product (Olaofe, 2013), the generation of higher value chemicals is needed to achieve a techno-economically feasible operation. A tandem catalytic process is proposed to valorize alkane activation using a cascade of bio-chemo reactions. Typically, chemical catalysts are synthesized using synthetic supports such as titanium dioxide or activated carbon. However, certain biological supports have a natural affinity for metal ions and have the ability to generate uniform, mono-dispersed nanoparticles, without the use of stabilizers or capping agents. The bacterial cell can be used as a support for chemo-catalysts that are easily accessible and cultivated. In this study, three different strains of Escherichia coli (E. coli) bacteria were considered as catalyst supports; namely E. coli DH5a, E. coli ATCC25922, E. coli BL21DE3. E. coli BL21DE3 was previously used as the host cell for the biocatalytic activation of alkanes. However, due to the known deficiency in hydrogenase for this strain, alternative E. coli strains (E. coli DH5a and E. coli ATCC25922) that could potentially also be used for the expression of this enzyme, were also considered. Reduction on these microbial supports required an electron donor (hydrogen and sodium formate) for manufacture of monometallic Palladium (Pd) and Gold (Au) nanocatalysts. Biosorption studies showed rapid adsorption of Pd and Au ions onto all microbial strains within 1- 5 minutes of cell exposure that was best described by the chemisorption of the metals onto amine, hydroxyl or thiol functional groups. Near-complete adsorption of Pd(II) occurred on all microbial strains, with E. coli ATCC25922 achieving the greatest capacity (ca. 94.4% mol/mol) at 5% (w/w) Pd loading. The adsorption efficiency declined to 27.9% (mol/mol) when the metal loading was increased to 25% (w/w) Pd. Reduction timeframes were dictated by the electron donor, with a hydrogen induced colour change noted within 20 minutes compared to 24 hours using sodium formate. Showing characteristics of ideal nanocatalysts, hydrogen-generated Pd(0) nanoparticles ranging from 3.0-3.5 nm and 3.9-9.3 nm in size were formed across all microbial strains at either 5% (w/w) or 25% (w/w) metal loadings. These nanoparticles were uniform and well-distributed within the cytoplasm. Clustering was most prevalent for the hydrogen-generated 25% (w/w) Pd loaded catalysts on E. coli ATCC25922 and E. coli BL21DE3. Minimal agglomeration and loss of Pd was observed on E. coli DH5a. In comparison to Pd(II), Au(III) was poorly adsorbed on all microbial strains with ca. 45.6% (mol/mol) and 33.7% (mol/mol) adsorbed on E. coli ATCC25922 at the 5% (w/w) and 25% (w/w) loadings. Bioreduction for this metal was only observed with hydrogen as the electron donor on E. coli ATCC25922 with irregularly-shaped Au(0) nanoparticles between 20 nm and 40 nm being formed. Catalyst activity was assessed using the oxidation of benzyl alcohol to benzaldehyde as a control reaction. No notable activity was detected for any of the Au catalysts. The greatest activity was observed by hydrogen-generated Pd catalysts at 25% (w/w) loading with conversions of up to 32.8±2.7% (mol/mol) and selectivity of 94.1±2.8% (mol/mol) across all microbial strains. For 1-octanol, hydrogen-generated 25% (w/w) Pd loaded E. coli ATCC25922 nanocatalysts achieved the highest activity to reach a conversion of 2.4% (mol/mol) with a selectivity of 82.7% (mol/mol) towards octanal. The addition of water limited byproduct poisoning to improve the conversion of 1-octanol to 9.6% (mol/mol) and 99.4% (mol/mol) selectivity to the aldehyde. The successful activity of the biofabricated catalyst on aromatic and aliphatic alcohols shows promise for tandem catalysis to valorize the alcohol product from bio- catalytic activated alkanes. Consequently, this approach can be used to improve the value of noctane via a bio-chemo catalytic cascade reaction where higher selectivity to the aldehyde can be reached.